SMSEI-SDN: A Suppression Method of Security Incident Impact for the Inter-Domain Routing System Based on Software-Defined Networking. (18th May 2021) - Zhu, Huihu; Qiu, Han; Zhu, Junhu; Chen, Di
Abstract : Security incidents such as natural disasters and power outages can cause inter-domain routing system regional failures, significantly impact the Internet's safety. Reducing the impact of security incidents is essential for maintaining the stability of the Internet. One of the major impacts of security incidents is that many UPDATE messages will generate, which may easily cause network oscillations. This paper presents the UPDATE messages analysis during the six security incidents and finds that many duplicates and invalid messages are the leading cause of network instability. To effectively process these UPDATE messages, this paper proposes an UPDATE message preprocessing algorithm by analyzing the UPDATE operating mechanism to remove duplicate and invalid messages. Aiming at the problem of slow route search in existing route update methods using software-defined networking (SDN), this paper designs a RIB hierarchical structure for multi-level retrieval and proposes SMSEI-SDN combination with current route update strategies. Experimental results show that when a security incident occurs, by removing duplicate and invalid messages, SMSEI-SDN can reduce the total number of messages by an average of 19% and a maximum of 34.9% within the 60 s of caching time. Besides, SMSEI-SDN can reduce the routing update time by more than 99.98% compared to existing methods. This work provides insights for network operators and researchers interested in security incident impact suppression in the inter-domain routing system.